Luminescence and non-radiative processes in lanthanide squarate hydrates - De Mello Donegá, C.; Ribeiro, Sidney José Lima [UNESP]; Gonçalves, R. R. [UNESP]; Blasse, G. (Elsevier, 1996)
The luminescence properties of solid hydrated lanthanide squarates (Ln2(C4O4)3(H2O) x; x = 8 or 13;Ln3+ = Gd, La, Eu, Tb, Pr) are reported for temperatures down to 4.2K. The luminescence of the squarate group is observed for the Gd3+ and La3+ compounds at low temperatures (below 150K). The Pr3+ compound does not show any emission at all, not even at 4.2K. This is ascribed to the quenching of the Pr3+ emission by multiphonon relaxation and/or concentration quenching. The quantum efficiencies of the 5D0 emission of Eu3+ and of the 5D4 emission of Tb3+ in these squarate complexes are strikingly different. Whereas the Tb3+ emission shows a temperature independent quantum efficiency of 50% upon ligand excitation, the Eu3+ emission is strongly quenched, showing a temperature dependent quantum efficiency of 0.8% at 4.2K upon ligand excitation. This quenching is ascribed to the low energy position of the charge-transfer state of Eu3+ in these compounds.
Keywords: A. inorganic compounds; D. luminescence; D. optical properties; Charge transfer; Hydrates; Ions; Luminescence; Optical properties; Quantum efficiency; Quenching; Concentration quenching; Lanthanide squarate hydrates; Ligand excitation; Multiphonon relaxation; Nonradiative processes; Rare earth compounds